Between Human and Machine: The Operating System. (1st September 2015) - Ellis, John
Abstract : This paper argues for an approach to the archaeology of technology that examines how skilled practitioners use technologies, using as an example "simulations" which reunite retired equipment with the people who used to use it and film the encounter. It proposes the metaphor of the "operating system" to highlight the mutual adaptation of human and machine in such circumstances, revealed through the filming of these encounters. An "operating system" transforms an artfully constructed assemblage of hardware materials into a productive mechanism. It exists between human and machine, and not in either party exclusively.